China's major Late Neolithic centres and the rise of Erlitou. (12th June 2019) - Zhang, Chi; Pollard, A. Mark; Rawson, Jessica; Huan, Limin; Liu, Ruiliang; Tang, Xiaojia
Abstract: Abstract : Recent archaeological survey and excavation in China have demonstrated that large sites of the late fourth and third millennia BC were situated not on the Central Plains—where the later dynastic centres were located—but along the Yangtze and lower Yellow River Basins. Their decline in the late third and second millennia BC coincided with the growth of sites to the north of the Central Plains. Evidence for settlement size and a new chronology constructed from radiocarbon dates emphasise discontinuities in the geographic distribution of settlements, combined with continuity in cultural practices of ritual feasts and the use of symbolic jades.